2015
DOI: 10.1007/s12149-015-0981-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between biodistribution of a novel thymidine phosphorylase (TP) imaging probe and TP expression levels in normal mice

Abstract: Objective Thymidine phosphorylase (TP) is a key enzyme in the pyrimidine nucleoside salvage pathway and its expression is upregulated in a wide variety of solid tumors. In mice, we previously observed high and specific accumulation levels of our TP imaging probe, radioiodinated 5-iodo-6-[(2-iminoimidazolidinyl)methyl]uracil (IIMU) not only in high-TP-expressing tumors, but also in the liver and small intestine. To clarify the reason for the high accumulation levels of radioiodinated IIMU in the liver and small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…5B). In our previous studies, we investigated the biodistribution of 125 I-IIMU and 123 I-IIMU in mice (25,27). The radiolabeled tracers mainly accumulated in the liver and small intestine, consistent with our present results.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…5B). In our previous studies, we investigated the biodistribution of 125 I-IIMU and 123 I-IIMU in mice (25,27). The radiolabeled tracers mainly accumulated in the liver and small intestine, consistent with our present results.…”
Section: Discussionsupporting
confidence: 90%
“…The radiolabeled tracers mainly accumulated in the liver and small intestine, consistent with our present results. Furthermore, we confirmed messenger RNA and protein levels of TP in various mouse tissues (27). We observed high TP expression in the liver and intestine, which corresponded to the observed high accumulation of radiolabeled IIMU (Supplemental Table 1).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In our previous studies, we clearly demonstrated that TYMP mRNA and protein were more highly expressed in the normal liver and small intestine than in the other organs including the heart, lung, stomach, spleen, kidney, large intestine, muscle, and brain [12]. Radiolabeled IIMU also accumulated mostly in the liver and small intestine of mice [9,10,12].…”
Section: Discussionmentioning
confidence: 84%
“…Thymidine phosphorylase (TYMP) is induced by TNF-α and is also identical to the platelet-derived endothelial cell growth factor (PD-ECGF) [7,8]. We previously synthesized radioiodine-labeled [10][11][12][13], and was safely administered in humans [14].…”
Section: Introductionmentioning
confidence: 99%